Exergy analysis for day lighting, electric lighting and space cooling systems for a room space in a tropical climate - Mahlia, T.M.I.; Taufiq, B.N.; Ong, K.P.; Saidur, Rahman (Energy and Buildings, 2011)
Turning off the electric lamp during available daylight will save electricity, while at the same time thermal energy from solar radiation transmitted through the window will increase the space-cooling load. Therefore, it is necessary to evaluate the whole system that includes not only the room space with the windows and the electric lighting systems, but also the air conditioning system. For analysis of the whole system using different types of energy (i.e. electricity, solar radiation, light emitted by lamps and thermal energy), it is important to take into account the quality of these different types of energy. The concept of entropy and exergy were applied in this analysis. The purpose of this study is to show the energy use for daylighting, electric lighting, and space cooling systems as a series of exergy input, output, and consumption and reveal how a daylighting system consumes solar exergy and how electric lighting and space cooling systems consume exergy from fossil fuel. The methodology to calculate the exergy consumption of the system during a given time was developed first. This method was then applied to the lighting and cooling for a typical room. The study found that electric lighting consumes the lowest amount of exergy while the space cooling consumes the highest amount of exergy for the system.